Determinants of Customer Satisfaction with Automated Teller Machine (ATM) Services: An Empirical Study of the Commercial Bank of Ethiopia, Nekemte Town - David Nemomsa; Tekalign Bekama; Gudata Abara Chali; Lalisa Mamo Abdisa (The Indonesian Institute of Science and Technology Research, 2026)
This study investigates the determinants of customer satisfaction with Automated Teller Machine (ATM) services at the Commercial Bank of Ethiopia (CBE) in Nekemte Town, within the context of Ethiopia’s rapidly expanding digital financial sector. ATMs play a vital role in improving banking accessibility and supporting financial inclusion, making customer satisfaction an important indicator of service quality and operational effectiveness. The research employed descriptive and explanatory research designs using quantitative methods. Primary data were collected from 184 active ATM users through structured questionnaires and analyzed using Pearson correlation and multiple linear regression techniques. The findings reveal that the reasonableness of transaction fees, accessibility and strategic location of ATMs, and the diversity of services available through ATM platforms significantly and positively influence customer satisfaction. Although respondents frequently reported technical malfunctions and operational interruptions, the variable representing the frequency of problems was not statistically significant in the regression model. This finding suggests that customers may have become accustomed to recurring technical issues within the banking system. The study concludes that improving ATM reliability, ensuring consistent machine functionality, expanding service features, and reviewing transaction fee structures are essential strategies for enhancing customer satisfaction and maintaining the bank’s competitive position in Ethiopia’s evolving digital banking environment.